Fulminant Brain Atrophy and Vasculitis on Vessel-Wall Imaging in Neuropsychiatric Lupus: Case Report and Literature Review - Mihaela Ionela SARBU; Nicolae SARBU (Archives of Rheumatology, 2020)
Brain atrophy, typically slowly progressive, is a hallmark of neuropsychiatric (NP) systemic lupus erythematosus (SLE). In this article, we report a case of a young female patient with previously diagnosed SLE, without known NPSLE, with abrupt neurological deterioration and rapidly progressive diffuse atrophy in a few months. A comprehensive diagnostic work-up and follow-up magnetic resonance imaging (MRI), including high-resolution advanced vessel-wall sequences, revealed underlying cerebral vasculitis. The novelty factors that the present report brings are the rapid progressive atrophy demonstrated on follow-up MRI in a patient with SLE, and the depiction of an underlying vasculitis on specific vessel-wall MRI techniques. We also reviewed the literature and discussed the main current applications of vessel-wall MRI sequences. The aim of the report is to recognize this dramatic form of presentation of NPSLE and the utility of the new MRI techniques for the diagnosis.